COVID-19 to Curb Positive Climate and Negative Recession - Vasudeo Pandharinath Zambare (Journal of Tropical Life Science, 2021)
A novel coronavirus originated COVID-19 a pandemic disease that is rapidly progressing and spreading the infection and death cases thorough out the globe [1-2]. It's an alarming situation for an individual's survival. As a remedial action, many countries opted for curfews or lockdown and serious actions were taken by the government to stop the spreading of novel coronavirus by shutting down private industries, schools, offices, and many more nonessential businesses. The outcome of lockdown resulted in almost negligible use of polluting vehicles, and industries which has direct setbacks on the global economy. The lockdown option showed a positive impact on health by minimizing the risk of COVID-19 infectivity as well as environmental rejuvenate in terms of tremendous improvement in air quality, sound pollution reduction, and ultimately the ozone layer healing. Thus, a precautionary measure taken against pandemic disease COVID-19 would have a positive impact on climate change at the global level. The financial activity has caught up and stock markets have to plummet alongside the declining environmental pollution including carbon emissions, sound, and natural water resources. It's the precise opposite of the drive towards a sustainable economy that many have been a campaigner for the future. But, a negative setback of COVID-19 toll of early deaths of family belongings, food scarcity, loss of jobs, struggle to earn the daily bread, family security, homesick and mental sickness. The widespread job losses would be in danger the income source of millions as businesses are struggling to cope with the limitations being put in place to control the deadly coronavirus during the lockdown period. Thus, I urge every national, public-private organization, research institutes to take early remedial strategies for the negatively affected community surveillance, health encouragement, education, food security, and job opportunities to control the 21st century’s biggest recession [3]. COVID-19 impacted improvement in the environmental air and water quality is a natural healing process and all nationals must maintain it in the future by adopting good hygiene and behavioral practices.